Antibiotic susceptibility of enterococci isolated from traditional fermented meat products - Barbosa, J. (2010)
Antibiotic susceptibility was evaluated for 182 Enterococcus spp. isolated from Alheira, Chouriça de Vinhais and Salpica˜o de Vinhais, fermented meat products produced in the North of Portugal. Previously, a choice was made from a group of 1060 isolates, using phenotypic and genotypic tests. From these, 76 were previously identified as Enterococcus faecalis, 44 as Enterococcus faecium, one as Enterococcus casseliflavus and 61 as Enteroccocus spp. In order to encompass several of the known chemical and functional classes of antibiotics, resistance to ampicillin, penicillin G, ciprofloxacin, chloramphenicol, erythromycin, nitrofurantoin, rifampicin, tetracycline and vancomycin was evaluated. All the isolates were sensitive to antibiotics of clinical importance, such as penicillins and vancomycin. Some differences in Minimal Inhibitory Concentrations (MICs) of antibiotics, could be associated with the enterococcal species.